Splenomegaly impacts prognosis in essential thrombocythemia and polycythemia vera: A single center study - Accurso, Vincenzo (Hematol Rep, 2019)
Splenomegaly is one of the major clinical manifestations of primary myelofibrosis and is common also in other chronic Philadelphia-negative myeloproliferative neoplasms, causing symptoms and signs and affecting quality of life of patients diagnosed with these diseases. We aimed to study the impact that such alteration has on thrombotic risk and on the survival of patients with essential thrombocythemia and patients with Polycythemia Vera (PV). We studied the relationship between splenomegaly (and its grade), thrombosis and survival in 238 patients with et and 165 patients with PV followed at our center between January 1997 and May 2019.